Review on the Design, Geometry and Mechanical Modeling of Piezoelectric Energy Harvesting Structures - , X. Zhao, Guoji Zuo, J. Chen (Archives of Current Research International, 2017)
In recent decades, with the increase of energy demand and the development of wireless and micro-electro-mechanical technology, research in the field of energy recovery has been paid more and more attention. Because of piezoelectric materials can transform mechanical strain energy into electrical charge, therefore, piezoelectric materials are the major method of energy scavenging. The research status of piezoelectric energy harvesting devices at domestic and overseas is presented in detail. This paper includes four aspects: Asingle-degree of freedom system, piezoelectric cantilever beam, energy harvesting circuit and topology optimization of energy harvester. The development perspective of the piezoelectric vibration energy harvester was summarized. The study will be helpful for the researchers who are engaged in the studying on the piezoelectric vibration energy harvesting.